Evaluación del modelo de simulación CERES-maize aplicado a una variedad de maíz en oxisoles de los Llanos Orientales de Colombia - Rivera Peña, M.; Amézquita Collazos, Edgar (2003)
Intensification of agricultural production on the acid-soil savannas of south America (mainly Oxisols) is constrained by the lack of diversity in acid (aluminum) tolerant crop germplasm, poor soil fertility and high vulnerability to soil physical, chemical and biological degradation. The model of simulation of growth and production of maize CERES-Maize DSSATv3.5, was evaluated to level of the Tropic. In 1993, a long-term field experiment was established in Carimagua, Colombia, (4°36 N, 71°19 W and 160 m altitude). The averange annual rainfall and temperature are 2200 mm and 26 °C, respectively, with a dry season from December to March in soils well drained have been defined as fine, kaolinitic, Isohyperthermic Haplustox (clay loam soil). In orden to study the influence of various systems on soil quality and system productivity on a savanna Oxisol. Initially there adjusted six genetic coefficients of the variety (Sikuani V110), which were calibrated by base in the experimentation in field in the localities of Carimagua, Palmira and Santander de Quilichao. The evaluation of the model presented narrow relation between the observed and the simulated data for the principal variables of response. The validation with base in information of the field experiment Culticore, it presented very narrow relation (r2 = 0.95), between the observed and the simulated data; which indicated, that the model explains good the production of grain and of biomass and other parameters as the epochs of flowering and days to harvest of the variety.